Preparation of Agricultural Extension Programs for the Food Crops and Horticulture Service, Langgosipi Village, Watubangga District, Kolaka Regency - Campina Illa Prihantini; Sugirah Hidayah Rauf; Masitah; Rahmat Tata Pratama (MEKONGGA: Jurnal Pengabdian Masyarakat, 2026)
The preparation of the 2026 Agricultural Extension Program in Langgosipi Village, Watubangga District, Kolaka Regency was carried out to design extension activities that are targeted, effective, and aligned with the needs of farmers. This activity employed participatory methods through village coordination, data collection, focus group discussions (FGDs), field surveys, and program formulation workshops. The evaluation results indicate that the village has strong potential in oil palm, coffee, and pepper commodities, supported by fertile land conditions and the use of superior seedlings. However, challenges remain in cultivation, post-harvest handling, marketing, and farmers’ technical capacity. Based on these findings, an extension program was developed that includes priority topics, implementation methods such as SLP, demonstration plots, and hands-on training, as well as a quarterly activity schedule. Overall, this program is expected to improve farmers’ productivity, product quality, and income, while also strengthening institutional capacity and the sustainability of agricultural practices in Langgosipi Village, Watubangga District, Kolaka Regency.